Pro dan Kontra Pancasila Sebagai Ideologi Negara (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Pancasila, as the ideology of the Indonesian nation, serves as the foundation for national and state life. However, its implementation journey is not without various pros and cons arising within society. This article aims to explore these dynamics through a comprehensive analysis of arguments supporting and opposing Pancasila as an ideology. On one hand, Pancasila is seen as a solution for uniting the diversity of the Indonesian nation and offers universal values such as unity, justice, and humanity. On the other hand, criticisms of Pancasila arise from various perspectives, including inconsistencies in its application and potential misuse in practical politics. Using a qualitative approach based on literature reviews and interviews with experts, this article concludes that the sustainability of Pancasila as an ideology depends on reinterpreting its values in the modern context and a strong commitment from all elements of the nation to implement it authentically.